Comparison of different bread types: chemical and physical parameters - Carocho, Márcio (2018)
In this work, the chemical and physical profile of 5 different bread types (Multicereal bread, Bavaria wheat bread, Wholemeal bread, Rye and Oat bread) were analysed in depth, namely the nutritional profile, individual fatty acids and soluble sugars through GC-FID and HPLC-RI, respectively, as well as the mineral profile, including micro and macroelements. Furthermore, a texture profile analysis was carried out in addition to the measurement of the crust colour. Each bread type showed a distinct profile, with Wholemeal and Bavaria having the lowest calories, and Oat the highest. Multicereal showed the highest amount of unsaturated fatty acids, while Wholemeal and Rye scored the least sodium amounts. The hardest bread was Rye and the easiest to chew were Oat and Bavaria breads. The latter was also the one with the darkest crumb of all the analysed breads. This work shows that bread can be baked to meet the needs and particularities of various kinds of diets.